Cardiopulmonary Resuscitation Techniques in the COVID-19 Pandemic Era: Literature Review - Arista Maisyaroh; Syaifuddin Kurnianto; Eko Prasetya Widianto; Primasari Mahardika Rahmawati; Retno Sari Nurhabibah (Health and Technology Journal (HTechJ), 2023)
Cardiac resuscitation in the era of the COVID-19 pandemic meets its challenges; in addition to the high prevalence of cardiac and pulmonary arrest events in these patients, the transmission rate to health workers who carry out CPR assistance is also relatively high. Therefore, it is necessary to develop CPR techniques in COVID-19 patients that can increase the success of CPR and reduce transmission rates. The purpose of the study was to explain how CPR techniques are in COVID-19 patients. The literature review method through data collection with an electronic database and evaluation of the literature review will use Critical Appraisal to test validity. Data collection with electronic databases was conducted through PubMed, Tailor, Francis, and Google Scholar with the keyword "CPR," "COVID-19," and " technique. "The data was successfully collected in the database of 548 articles then filtered the inclusion and exclusion criteria into ten pieces; then the article passed the Critical Appraisal test. Hasil Literature review CPR technique in covid patients added is the use of PPE level C/3; The recommended compression depth is 2-2.4 inches (5-6cm); manual chest compression is described as effective when administered in the middle of the chest, at a rate of 100-120 minutes. , The recommended position is prone and supine.